Synthesis and characterization of CeO2/Bi2O3/gC3N4 ternary Z‐scheme nanocomposite. Issue 5 (1st July 2020) - Devi K R, Sunaja; Mathew, Sandra; Rajan, Revathy; Georgekutty, Josna; Pinheiro, Dephan; U, Ananthapadmanabhan; M, Sundararajan
Abstract: An effective and facile phytogenic method was used to prepare CeO2 /Bi2 O3 and CeO2 /Bi2 O3 /gC3 N4 composites using Eichhornia crassipes phytoextract. The synthesized catalysts were characterized using techniques such as XRD, FTIR, UV‐DRS, PL, SEM‐EDAX, XPS, zeta potential, and TGA. These catalysts showed diverse photocatalytic and optical properties due to the alteration in the bandgap. The synthesized composites exhibited good photocatalytic activity by degrading Malachite green (MG) dye. The increase in the photocatalytic activity could be attributed to the p ‐ n heterojunction of the catalysts with efficient charge separation and strong oxidative ability. The modified photocatalysts showed excellent catalytic activity and reusability under visible light. The superior efficiency and its applications in environmental remediation make these catalysts a potential candidate for photocatalysis. Abstract : CeO2 /Bi2 O3 /gC3 N4 Z‐scheme nanocomposite.